Learning Race and Racism While Learning: Experiences of International Students Pursuing Higher Education in the Midwestern United States. (July 2017) - Mitchell, Donald; Steele, Tiffany; Marie, Jakia; Timm, Kathryn
Researchers have documented how race and racism influence the college experiences of U.S. citizens. However, research on the ways that race and racism affect international students warrants similar attention. This qualitative study explored how international students learned about U.S. concepts of race and racism and how such concepts shaped their college experiences. The participating international college students learned about U.S. concepts of race and racism through media, relationships, formal education, and lived experiences. They defined these concepts in varying ways and had varying racial ideologies.